IMPROVING THE STUDENTS’ ABILITY TO WRITE DESCRIPTIVE TEXTS THROUGH FOUR SQUARE WRITING METHOD - Ilmiah Ilmiah; Supardin Supardin; Hasnawati Latief; Muhammad Basri Dalle (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2017)
Writing is a difficult skill for the students at SMPN 26 Makassar. It could be seen from the result of a diagnostic test which showed the ability of the second year students of SMPN 26 Makassar in writing paragraphs was still poor. The students were unable to express their ideas well in making descriptive texts. The research used Classroom Action Research that consisted of planning, action, observation, and reflection. It conducted in two cycles in which each cycle comprised four meetings. The subjects of this research were 28 students of the second year students of SMPN 26 Makassar.The findings indicated that the students’ ability to write descriptive text in cycle 1 has not reached the score target because the mean score of the students was 66.52 that classified as “fairly good” whereas, In cycle 2 the students’ mean score was 75.26. It indicated that the score target has been reached and classified as “Good”. Therefore, the researcher suggested the English teacher apply Four Square Writing Method as one of the alternative ways of teaching writing subject in the classroom especially in teaching the descriptive text.